Mobility across firms and occupations among graduates from apprenticeship - Fitzenberger, Bernd [Verfasser]; Licklederer, Stefanie [Verfasser]; Zwiener, Hanna [Verfasser] (My University, 2015)
"Distinguishing carefully between mobility across firms and across occupations, this study provides causal estimates of the wage effects of mobility among graduates from apprenticeship in Germany. Our instrumental variables approach exploits variation in regional labor market characteristics. Pure firm changes and occupation-and-job changes after graduation from apprenticeship result in average wage losses, whereas an occupation change within the training firm results in persistent wage gains. For the majority of cases a change of occupation involves a career progression. In contrast, for job switches the loss of firm-specific human capital seems to dominate." (Authors' abstract, BIBB-Doku)
Vorab erschienen als Diskussionspapier "IZA DP No. 9006", http://ftp.iza.org/dp9006.pdf [Zugriff 27.7.2015].
Keywords: G 1.3.3 Bildungs- & Erwerbsbiografien; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 1.3.3.3 Mobilität; Ausbildungsabsolvent; Berufsverlauf; Einkommen; Einflussfaktor; Berufliche Mobilität; Berufswechsel